Verkkoapteekkien tekninen toteutus ja sääntelyn vaikutukset Suomessa - Lillbacka, Matias (2025)
This study examines the technical solutions used in Finnish online pharmacy systems and how legislation affects their implementation, development, and everyday operations. The number of online pharmacies has increased in recent years, accompanied by a growing complexity in regulatory requirements. The operations are governed by the Finnish Medicines Act, Fimea’s guidelines, and EU legislation. The research was conducted as a multi-method study combining docu-ment analysis and expert interviews. The document analysis focused on how legislative requirements influence technical implementation and practical pro-cedures. A thematic analysis was carried out based on five expert interviews to explore how regulation shapes development work and operational practices in real-world settings. The results indicate that the technical implementation of online pharma-cies relies on a broad range of system integrations, and that system providers play a central role in ensuring compliance with regulatory demands. Regula-tion was often perceived as ambiguous, leading to challenges in technical exe-cution and highlighting the need for deeper collaboration between authorities and system vendors. The study brings to light the interplay between regulation and technical implementation and identifies potential areas for improvement. At the same time, it contributes new knowledge to a field that has thus far been relatively underexplored.